2015
DOI: 10.1002/hipo.22494
|View full text |Cite
|
Sign up to set email alerts
|

Oscillatory patterns in hippocampus under light and deep isoflurane anesthesia closely mirror prominent brain states in awake animals

Abstract: The hippocampus exhibits a variety of distinct states of activity under different conditions. For instance the rhythmic patterns of activity orchestrated by the theta oscillation during running and REM sleep are markedly different from the large irregular activity (LIA) observed during awake resting and slow wave sleep. We found that under different levels of isoflurane anesthesia activity in the hippocampus of rats displays two distinct states, which have several qualities that mirror the theta and LIA states… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 56 publications
(89 reference statements)
2
25
1
Order By: Relevance
“…Whereas we observed increased hippocampal delta oscillations, hippocampal delta activities have been observed so far only in primates and humans but not rodents (64,65). Previous studies in rodents showed that theta-like oscillations in the hippocampus shifted to lower frequencies (i.e., delta range) during light anesthesia (∼1.0% isoflurane) (66,67). This finding suggests that our increased delta oscillation results might arise from increased theta-like oscillations after low-frequency stimulation.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…Whereas we observed increased hippocampal delta oscillations, hippocampal delta activities have been observed so far only in primates and humans but not rodents (64,65). Previous studies in rodents showed that theta-like oscillations in the hippocampus shifted to lower frequencies (i.e., delta range) during light anesthesia (∼1.0% isoflurane) (66,67). This finding suggests that our increased delta oscillation results might arise from increased theta-like oscillations after low-frequency stimulation.…”
Section: Discussioncontrasting
confidence: 64%
“…An EEG study in humans reported EEG differences under anesthesia and sleep/wake conditions, but the authors observed sleep oscillations (i.e., slow and delta dominant) under anesthesia (80). Such oscillations were also found in rodent studies during extracellular and/or intracellular recordings (67,81,82). Taken together, these studies highlight the robust presence of lowfrequency activity in brain-wide interactions under various states, including anesthetized and sleep conditions.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…There is also evidence that adequate depth of isoflurane anesthesia can drive the rodent hippocampus into a SPW-like state with bursts of inputs into stratum radiatum that demonstrate a similar pattern to CA3-derived SPW observed in the awake rodent (Lustig et al, 2015). We also observe regular bursts of synchronized input into stratum radiatum in the isoflurane anesthetized pig that have the typical phase reversal across the pyramidal cell layer expected of CA3-derived SPWs.…”
Section: Discussionsupporting
confidence: 64%
“…These waves demonstrated a phase reversal at the pyramidal layer, at the bottom of stratum radiatum reminiscent of sharp waves described in the awake rodent hippocampus (Bragin et al, 1995b;Buzsáki et al, 2003), and again at dentate gyrus middle molecular layer (arrows). It is possible that these are regular sharp-wave-like (SPWlike) events representing synchronized pre-synaptic currents from CA3 projections, as SPW have been shown to take on an oscillatory characteristic under isoflurane anesthesia in rodents (Lustig et al, 2015).…”
Section: Simultaneous Laminar Field Potentials and Single Unit Activimentioning
confidence: 99%